Disharmonization Of Corporate Criminal Liability Arrangements In Forestry Law - Mangkunegara, RM. Armaya (Publikasi Indonesia, 2023)
The dynamics of changes in the Act Number 41 of 1999 on Forestry have an impact on the disharmonization of arrangements regarding corporate criminal liability. Referring to the principle of legality, criminal liability must refer to the clarity of the formulation in law. Disharmonization of corporate criminal liability arrangements in forestry law can be a problem in the realm of law enforcement. This research aims to provide an analytical description related to the harmonization of corporate criminal liability arrangements in forestry law. The method used is fully conducted through literature study associated with legal theories related to corporate criminal liability. The results showed that there are several provisions of corporate criminal liability in forestry law that are not synchronized with each other. Therefore, harmonization steps are needed, which in theory and practice. Suggestions that can be submitted to the House of Representatives are: There needs to be fundamental changes, especially regarding corporate criminal liability in forestry law which is regulated separately in the Forestry Law.